Mediterranean Plants - Rhizopoulou, Sophia; Karatassiou, Maria; Levizou, Efi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Plants grown and exposed to Mediterranean climatic conditions are a source of information of a natural heritage. Mediterranean plants have been presented as vehicles for expressing historical knowledge and environmental attributes; scientific reports have given us important insights into plant growth, structure, and function. With the current environmental and social threats, mainly posed by expanding touristic and anthropogenic activities, the importance of Mediterranean plants will once again be appreciated. In this book, the function, structure, diversity, biogeography, conservation, seasonality, and interactions of Mediterranean plants with the abiotic and biotic environment are highlighted.